НАЎАЙЫ ҲӘМ БУХАРА АЙМАҒЫ ҚАРАҚАЛПАҚ ЖЫРАЎЛАРЫ ҲАҚҚЫНДА БИР-ЕКИ АЎЫЗ СӨЗ - Эгамкулова, Г.М. (SCIENCE and SOCIETY, 2021)
This article provides some information about the Karakalpak jiravic craft, well-known jiravs who lived and worked in Bukhara and Navoi regions. The process of development of Zhirov schools in these regions is analyzed.